The allocation of assimilated carbon to shoot growth: in situ assessment in natural grasslands reveals nitrogen effects and interspecific differences - Xiao, Ying Gong; Berone, German Dario; Agnusdei, Monica Graciela; Rodríguez Palma, Ricardo Manuel; Schäufele, Rudi; Lattanzi, Fernando Alfredo (2018)
In grasslands, sustained nitrogen loading would increase the proportion of assimilated carbon allocated to shoot growth (A shoot), because it would decrease allocation to roots and also encourage the contribution of species with inherently high A shoot. However, in situ measurements of carbon allocation are scarce. Therefore, it is unclear to what extent species that coexist in grasslands actually differ in their allocation strategy or in their response to nitrogen. We used a mobile facility to perform steady-state 13C-labeling of field stands to quantify, in winter and autumn, the daily relative photosynthesis rate (RPR~tracer assimilated over one light-period) and A shoot (~tracer remaining in shoots after a 100 degree days chase period) in four individual species with contrasting morpho-physiological characteristics coexisting in a temperate grassland of Argentina, either fertilized or not with nitrogen, and either cut intermittently or grazed continuously. Plasticity in response to nitrogen was substantial in most species, as indicated by positive correlations between A shoot and shoot nitrogen concentration. There was a notable interspecific difference: productive species with higher RPR, enhanced by fertilization and characterized by faster leaf turnover rate, allocated ~20 % less of the assimilated carbon to shoot growth than species of lower productivity (and quality) characterized by longer leaf life spans and phyllochrons. These results imply that, opposite to the expected response, sustained nitrogen loading would change little the A shoot of grassland communities if increases at the species-level are offset by decreases associated with replacement of ‘low RPR-high A shoot’ species by ‘high RPR-low A shoot’ species.